Amino Acids Profile of Loranthus europaeus from Different Countries - Ali, Haval; Karatas, Fikret; Özer, Dursun; Saydam, Sinan (My University, 2023)
In this study, the amounts of amino acids in Loranthus europaeus samples grown in different regions (Türkiye, Iran and Iraq) were analyzed by High Performance Liquid Chromatography (HPLC).The results indicate that, aspartic acid, serine, alanine, proline and tyrosine were found to be highest in samples grown in Iran, glutamic acid, asparagine, glycine, and glutamine were found in Loranthus europaeus samples grown in Iraq, and cysteine was found to be highest in samples grown in Türkiye. It can be said that Loranthus europaeus growing in Turkey is poor in terms of asparagine, serine, glycine, glutamine, alanine, proline and tyrosine, on the other hand aspartic acid found to be lowest in samples from Iraq and glutamic acid is the lowest samples from Iran. It was obtained that while Loranthus europaeus samples grown in Iran is the richest in terms of total essential amino acids, on the other hand samples grown in Türkiye is the poorest. Total amino acids content was highest in Iraqi samples and the lowest in Turkish samples. It can be said that the variation of essential and non-essential amino acids contents between regions could be due to geographical, and ecological differences.
Keywords: HPLC; Amino acids; Loranthus Europaeus; Total amino acid